PERUBAHAN STATUS ORGANISASI PAPUA MERDEKA (OPM) MENJADI ORGANISASI TERORIS OLEH PEMERINTAH INDONESIA: SEBUAH ANALISIS DALAM PERSPEKTIF HAM - Kusuma, Ardli Johan; Setiawan, M. Chairil Akbar; Ilmar, Anwar; Situmeang, Nurmasari (Program Studi Ilmu Pemeritahan Fakultas Ilmu sosial dan Ilmu Politik Universitas 17 Agustu, 2022)
In dealing with the conflict in Papua, the Indonesian government has made various efforts, one of which is changing the status of the Free Papua Organization (OPM) which was originally defined as an armed criminal group, then changed to a terrorist group. The focus of this research is the change in the status of the OPM to the terrorist organization. This research is analytical with an explanatory approach that explains the reasons behind the policy taken by the Indonesian government to change the status of OPM to a terrorist organization. In collecting data to build arguments in this study using a literature study approach, where data is obtained from various literature sources such as books, journals, documents or reports, and also from internet sources that are considered relevant. The findings of this study can be illustrated that the Indonesian government's policy to change the status of the OPM to a terrorist organization has been motivated by several reasons, including: OPM has met the definitive requirements as a terrorist; expanding the space for the Indonesian government to deal with the OPM, including facilitating the tracking and blocking of funding for the OPM movement; To gain legitimacy from any efforts or steps taken to confront OPM; Using the